A middle-range theory self-care in chronic diseases:a reflection for application in the context of cardiovascular diseases (Research, Society and Development, 2020)
Chronic Non-Communicable Diseases (NCDs), including mainly cardiovascular diseases, constitute a serious public health problem, contributing to loss of quality of life, premature deaths, high expenses and limitations. Therefore, it is a challenge in the health field and for nurses, the development of educational practices to promote self-care. Therefore, the objective was to reflect on the medium-range theory for self-care in chronic diseases. It is a theoretical-reflective study, with data collection from September to October 2020 in databases, without limitation of time frame, resulting in 03 (three) studies on cardiovascular diseases. 02 (two) axes were established for this reflection, called "Axis-Definition" for the medium-range theories in the health area and "Axis-Purpose" of the Medium-Range Theory of Self-Care in Chronic Diseases. And in view of this analysis, it can be said that there is enormous potential for applicability by nurses of the Medium Reach Theory of Self-Care in Chronic Diseases with heart disease, since it gathers fundamental principles of self-care, such as maintenance, monitoring and management.